2014
DOI: 10.1039/c4lc00342j
|View full text |Cite
|
Sign up to set email alerts
|

A microtensiometer capable of measuring water potentials below −10 MPa

Abstract: Tensiometers sense the chemical potential of water (or water potential, Ψw) in an external phase of interest by measuring the pressure in an internal volume of liquid water in equilibrium with that phase. For sub-saturated phases, the internal pressure is below atmospheric and frequently negative; the liquid is under tension. Here, we present the initial characterization of a new tensiometer based on a microelectromechanical pressure sensor and a nanoporous membrane. We explain the mechanism of operation, fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 53 publications
(63 reference statements)
1
40
0
1
Order By: Relevance
“…This may lead one to expect system dryout, however, recent reports have shown that transpiration can be self-stabilizing when the menisci recede far enough within the nanopores that the local humidity is increased to a value where ≤ | | P P K L , max 34,36 . This necessary balance between the Kelvin and Laplace pressures to stabilize the free interface is well understood and has been thoroughly characterized 25,[32][33][34] . Curiously lacking in the synthetic tree literature, however, is a second pressure balance required for conservation of mass.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may lead one to expect system dryout, however, recent reports have shown that transpiration can be self-stabilizing when the menisci recede far enough within the nanopores that the local humidity is increased to a value where ≤ | | P P K L , max 34,36 . This necessary balance between the Kelvin and Laplace pressures to stabilize the free interface is well understood and has been thoroughly characterized 25,[32][33][34] . Curiously lacking in the synthetic tree literature, however, is a second pressure balance required for conservation of mass.…”
Section: Resultsmentioning
confidence: 99%
“…In the same year, Noblin et al evaporated water from PDMS to pump water across an array of microfluidic channels 26 . Several follow-up papers characterized the thermophysical properties of the negative pressure water, including its metastability 27 , cavitation dynamics [28][29][30][31] , and using nanoporous silicon (≈3 nm diameter pores) to achieve up to 100 MPa of negative Laplace pressure [32][33][34] . For all of these tree-on-a-chip devices, transpiration is no longer used to pump water against gravity, but rather to drive flows in micro-channels or as a platform for studying the fundamental properties of negative pressure water.…”
mentioning
confidence: 99%
“…38 By integrating sensors into a synthetic leaf, it can even be used as a microtensiometer for measuring the water potential of synthetic or natural plants. 39,40 However, the menisci within synthetic leaves are known to become unstable beneath a critical relative humidity. The magnitude of this critical humidity can be quite high, which poses a severe obstacle for using synthetic trees in real-life environments.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, a new type of small tensiometer has been developed for the measurement of water potential in plants. The device has a microelectromechanical (MEM) pressure sensor and a nanoporous membrane [52], and it is small enough to be embedded into plant stems to directly measure plant water potentials, down to about −10 MPa. According to the developers, this new technology has potential for automatic and continuous measurement of water potential in plants under field conditions.…”
Section: Leaf and Stem Water Potentialmentioning
confidence: 99%